Cytokines as plasma markers of abdominal aortic aneurysm - Treska, V; Topolcan, O; Pecen, L (Clinical chemistry and laboratory medicine, 2000)
UNLABELLED: The pathogenesis of abdominal aortic aneurysms (AAA) is a complex process in which atherosclerosis and inflammation play a leading role. Cytokines are important mediators of both processes. The aim of our study was to determine whether plasma levels of cytokines which are most involved in AAA pathogenesis can be used as endogenous markers of AAA development, and thus to facilitate the decision on surgical intervention in cases when this is clinically unclear (e.g. small AAA). In the prospective study a total of 90 patients with AAA were examined. These patients were divided into the following groups according to symptoms and AAA diameter: symptomatic AAAs, including ruptures (n=16); asymptomatic AAAs (n=74); AAAs with a diameter of up to 5 cm (n=30), AAAs of 5-8 cm (n=38), and AAAs with a diameter over 8 cm (n=22). The average age of the patients was 70.7 (56-82) years. The male to female ratio was 4:1 (71:19). A control group consisted of 30 healthy individuals of similar age and sex presentation with no manifestation of atherosclerosis. Plasma levels of cytokines were assessed in venous blood by means of radio- or enzymo-immunoassay. Statistical processing of the results was conducted with ANOVA and Wilcoxon tests with Spearman correlation, where p<0.05 was considered to be statistically significant. Plasma concentrations of cytokines were significantly higher in AAA patients than in healthy individuals. In AAA patients the tumour necrosis factor-alpha (TNF-alpha) and interleukin (IL-8) levels were low in large and in symptomatic AAAs. IL-6 levels were increased with increasing AAA diameter and symptoms. IL-8 levels (p<0.05) showed a statistically significant correlation with the diameter, and TNF-alpha (p<0.05) with the symptoms of AAA. IL-1beta, IL-2 and IL-6 did not show any significant changes with different AAA diameter or symptomatology. IN CONCLUSION: IL-8 and TNF-alpha can be used as endogenous markers of the process of AAA development, in deciding for either surgical or endovascular treatment of patients when the clinical indication is not entirely clear.
Keywords: Male; biologické markery; aneurysma břišní aorty; Tumor Necrosis Factor-alpha; Interleukins; interleukiny; Biomarkers; Aged; Prospective Studies; mužské pohlaví; senioři; senioři nad 80 let; lidé; ženské pohlaví; Humans; Aged, 80 and over; TNF-alfa; Aortic Aneurysm, Abdominal; Female; lidé středního věku; Middle Aged; prospektivní studie